Attentional functions in dorsal and ventral simultanagnosia. - Duncan, J; Bundesen, C; Olson, A; Humphreys, G; Ward, R; Kyllingsbæk, S; van Raamsdonk, M; Rorden, C; Chavda, S (2003)
Whole report of brief letter arrays is used to analyse basic attentional deficits in dorsal and ventral variants of simultanagnosia. Using Bundesen's Theory of Visual Attention (TVA), a number of previous theoretical suggestions are formalised and tested, including primary deficit in processing more than one display element, attentional stickiness, foveal bias, and global weakness of the visual representation. Interestingly, data from two cases, one dorsal and one ventral, show little true deficit in simultaneous perception, or selective deficit in those TVA parameters (short-term memory capacity, attentional weighting) specifically associated with multi-element displays. Instead there is a general reduction in speed of visual processing (processing rate in TVA), effective even for a single display element but compounded when two or more elements compete.